Microaerophilic growth and induction of the photosynthetic reaction center in Rhodopseudomonas viridis. - Lang, F S (1989)
Rhodopseudomonas viridis was grown in liquid culture at 30 degrees C anaerobically in light (generation time, 13 h) and under microaerophilic growth conditions in the dark (generation time, 24 h). The bacterium could be cloned at the same temperature anaerobically in light (1 week) and aerobically in the dark (3 to 4 weeks) if oxygen was limited to 0.1%. Oxygen could not be replaced by dimethyl sulfoxide, potassium nitrate, or sodium nitrite as a terminal electron acceptor. No growth was observed anaerobically in darkness or in the light when air was present. A variety of additional carbon sources were used to supplement the standard succinate medium, but enhanced stationary-phase cell density was observed only with glucose. Conditions for induction of the photosynthetic reaction center upon the change from microaerophilic to phototrophic growth conditions were investigated and optimized for a mutant functionally defective in phototrophic growth. R. viridis consumed about 20-fold its cell volume of oxygen per hour during respiration. The MICs of ampicillin, kanamycin, streptomycin, tetracycline, 1-methyl-3-nitro-1-nitrosoguanidine, and terbutryn were determined.